HUBUNGAN RELIGIUSITAS DENGAN PSYCHOLOGICAL WELL-BEING PADA ANGGOTA SATPAMWAL DENMA MABES TNI: HUBUNGAN RELIGIUSITAS DENGAN PSYCHOLOGICAL WELL-BEING PADA ANGGOTA SATPAMWAL DENMA MABES TNI - Hamidah, Tjitjik; Gamal, Hendri (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2018)
Abstract A lot of workload that must be handled by the Satpamwal Command Guard Denma TNI have caused excessive work pressure and have an impact on psychological well-being. This study aims to determine the relationship between religiosity and psychological well-being on the soldiers of the Satpamwal Denma TNI Headquarters. By using incidental sampling, 45 respondents were obtained. Data retrieval uses the scale of religiosity (Glock & Stark, 1996) and the scale of psychological well-being (Ryff & Keyes, 1995) with likert models. After being tested, there were 41 valid items from 45 items of religiosity scale and 33 valid items from 40 items on the scale of psychological well-being. The results of data analysis using the bivariate correlation method, concluded that there was a significant relationship with the positive direction between religiosity and psychological well-being.